Karl Polanyi. El Racionalismo Económico Como Motor De La Utopía Liberal - Goikoetxea Berdonces, Maialen (KARL POLANYI. THE ECONOMIC RATIONALISM AS THE MOTOR OF THE LIBERAL UTOPIA., 2018)
Karl Polanyi's main thesis is the effective separation of society and economy, placing the economy above the society. This artificial separation will be carried out by a series of theoretical tools and mechanisms -the introduction of fictitious goods and economic rationalism as a social premise- that will blind an overall view of the social panorama, focusing only on the economic aspects of it, causing that way, an unprecedented human crisis. (English)
Keywords: capitalism; capitalismo; economic rationalism; fictitious goods; liberal utopia; mercancías ficticias; racionalismo económico; utopía liberal

The Double Movement in Polanyi and Hayek: Towards the Continuation of Life - Faria, Filipe Nobre (Ethics, Politics & Society, 2018)
Karl Polanyi’s double movement is a dialectical process characterized by a continuous tension between a movement towards social marketization and a movement towards social protectionism. Notably, Polanyi condemns the former movement while defending the latter. Without using the term “double movement”, F.A Hayek’s theory of social evolution acknowledges the same phenomenon but reaches different normative conclusions. While for Polanyi the marketization of society is a utopia with dystopian consequences, Hayek’s evolutionary explanation of this dialectical process asserts that there is no alternative to a market oriented society. Both authors defend that their favoured movement is the one that truly supports the continuity of life. This article compares the authors’ normative readings of the double movement and concludes that, from an evolutionary perspective, Polanyi’s conclusion possesses a robustness that Hayek’s postulate lacks.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; double movement

Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Keywords: boundary struggle; capitalism; political philosophy; triple movement

Mercados, historia y teleología: reflexiones desde la noción de «doble movimiento» de Karl Polanyi - Polo Blanco, Jorge Polo (CONVIVIUM, 2018)
En el presente trabajo mostraremos que la filosofía liberal operó en muchas ocasionesa través de un esquema teleológico, desde el cual entendía que la espontaneidad delmovimiento histórico conducía de forma natural hacia una economía de mercados libres.Semejante interpretación tenía que presuponer otra controvertida tesis, a saber, que lascategorías que informan la racionalidad práctica dentro de una sociedad de mercado no sonuna simple contingencia histórica, sino que responden a la estructura lógica de cualquieracción humana; esto es, como si toda acción humana, en cualquier tiempo y lugar, hubiesefuncionado a través de una misma lógica inmutable que coincidía, en lo esencial, con laracionalidad típica de una economía de mercado. Para adentrarnos críticamente en estaproblemática utilizaremos la obra de Karl Polanyi, cuya obra se oponía frontalmente a estasdos tesis manejadas por el liberalismo económico.
Keywords: MISES, Ludwig von; doble movimiento; double movement; economía de mercado; historical teleology; market economy; teleología histórica